Higher Prevalence of Periodontitis and Decayed, Missing and Filled Teeth in Patients with Psoriasis - Barros, Fabiana Cervo de; Sampaio, Janaina Nunes; Figueredo, Carlos Marcelo da Silva; Carneiro, Sueli; Fischer, Ricardo Guimarães (European Journal of Dentistry, 2020)
Objective The aim of this study is to describe the prevalence and severity of periodontitis and decayed, missing and filled teeth (DMFT) index in patients with psoriasis. As a secondary aim, verify if periodontitis was a risk indicator for psoriasis.Materials and Methods A total of 69 patients diagnosed with psoriasis (48.7 ± 14.6 years) and 74 healthy controls (40.3 ± 12.9 years) participated in the study. Probing pocket depth, clinical attachment loss (CAL), bleeding on probing, plaque index, and DMFT index were measured in all subjects. Periodontitis was defined as the presence of at least three interproximal sites with CAL ≥3 mm in different teeth and severe periodontitis should involve at least two interproximal sites in different teeth with CAL ≥5 mm.Statistical Analysis The Mann–Whitney test was used to analyze the demographics and the clinical data. The significance level was 5%. A multivariate logistic regression was conducted, and the odds ratio were calculated to express the risk to develop psoriasis.Results Patients with psoriasis had significantly more sites with CAL ≥3 mm (p < 0.03) and CAL ≥5 mm (p < 0.0001), less sites with plaque (p < 0.0001), fewer teeth (p < 0.0001), and a high DMFT index (p < 0.02) as compared with controls. Severe periodontitis was significantly more frequent (87.1% × 58.1%) and was a risk indicator for psoriasis after adjusting for sex, age, race, and smoking habits (odds ratio: 3.7, 95% confidence interval: 1.5–9.0, p < 0.003).Conclusion Patients with psoriasis have higher prevalence of severe periodontitis and higher DMFT than control patients. Severe periodontitis may be a risk indicator for psoriasis.
Keywords: psoriasis; periodontal disease; decayed, missing and filled teeth index; chronic diseases